Legible bodies: race, criminality and colonialism in South Asia - Anderson, Clare (Berg, 2004)
Introduction: textualizing the Indian criminal body -- Inscribing the criminal body: the penal tattoo -- 'Surely there is more in this than mere ornament': ethnography, surveillance, and the decorative tattoo -- The question of convict dress -- Voir/savoir: photographing, measuring and fingerprinting the Indian criminal -- Emperors of the Lilliputians: criminal physiology and the Indian social body